Mamba & Mambacita forever - Bryant, Vanessa, 1982- (MCD / Farrar, Straus and Giroux, 2025)
"A beautiful and moving testament to the enduring life of Kobe Bryant and the Mamba Mentality"-- Provided by publisher.